PENGEMBANGAN RUBI WEB (RUMAH BIOLOGI WEB) DALAM KONSEP KEANEKARAGAMAN HAYATI THE DEVELOPMENT OF RUBI WEB (RUMAH BIOLOGI WEB) IN BIODIVERSITY CONCEPT - Mahrawi Mahrawi; Indria Wahyuni; Dwi Ratnasari; Yunvida Istiana (AL-ULUM: JURNAL SAINS DAN TEKNOLOGI, 2022)
This study aims to develop a web-based learning media, namely RUBI WEB (House of Biology Web) in the concept of biodiversity. The research method used in this research is a modified development research method from Borg & Gall whose stages consist of information gathering, planning, product development, and initial field trials.  Aspects of the assessment of the material assessed include aspects of material and aspects of language, then aspects of media assessment that are assessed include aspects of software engineering, aspects of instructional design, and aspects of visual communication. The results of the material feasibility test by material experts obtained a percentage value of 80% and media feasibility tests by media experts obtained a percentage value of 83.4%. The results of the user response test by students obtained a percentage value of 86. Therefore, it can be interpreted that the RUBI WEB website learning media in the concept of biodiversity is included in the grade A+ category with a range of percentile ratings between 96-100%, best imaginable adjectives category, acceptable level of acceptance, and NPS (Net Promotore Score) in class promoter, i.e. users are satisfied and loyal to RUBI WEB media, so that they can make users want to recommend this media to others.